Hjalmar Branting och Hans Livsgärning - Höglund, Zeth (Stockholm : Tidens Förlag, 1939)
Bibliotheek Camille Huysmans
Zweeds
Monografie
Keywords: Branting, Hjalmar; Sveriges Socialdemokratiska Arbetareparti (SAP).; Zweden